Linear relationships between root and above-ground traits in common bean segregant generations - Cerutti, Paulo Henrique; Carbonari, Luan Tiago dos Santos; Joaquim Junior, Carlos Zacarias; Guidolin, Altamir Frederico; Coimbra, Jefferson Luís Meirelles (Revista de Ciências Agroveterinárias, 2024)
The correlation estimation and its partition into cause and effect is seen as a valuable tool in obtaining gains from selection in plant breeding. This allows the anticipation of choosing the best genotypes. Thus, the objective of this study was to consider indirect selection for simultaneous improvement of root and above-ground traits in segregating common bean populations. The experiment was carried out in the 2021/22 season, considering six common bean genotypes, two parents and four segregating generations (F2, F3, F4 and F5), under a lattice design. Root system traits were measured by two phenotyping methods, called Shovelomics and WinRHIZO. The aerial part traits evaluated were chlorophyll content, plant height, stem diameter, first pod height insertion and yield components (number of pods, number of grains and weight of grains per plant). Correlation analysis and cause and effect analysis (path analysis) were performed. Significant correlation estimates (τ) were found between root and aerial traits, with emphasis on chlorophyll B content with left horizontal length (τ = -0.22) and chlorophyll A content with total root length (τ = 0.24). The unfolding of these estimates by path analysis indicated that the chlorophyll A content has a correlation and a high direct effect on the total length of roots and that the total chlorophyll content indirectly influences the left and right horizontal root lengths. This fact makes it possible to obtain gains with the selection of improved common bean plants for root system based on the direct and indirect evaluation of chlorophyll contents, easily measured in the aerial part of the plants. This allows the optimization of time and resources in breeding programs, aiming at obtaining agronomically superior plants.